Biologia molecular in silico: da bioinformática à dinâmica molecular e bioquímica quântica com aplicações na saúde humana - Amaral, Jackson Lima (2022)
In bio logy an d other experimental sciences, in silico research (from the pseudo Latin 'in silicon', which in Latin would be 'in silício i s carried out with the computer as the main auxiliary tool, which contrasts with research carried out u s ing whether l iving organis ms in vitro and in vivo . In this thesis, we describe the fundamentals of Molecular Biology in silico , giving a succinct de sc ri ption of what Bioinform atics, Molecular Dynamics, and Quantum Biochemistry are in the context of the re s earch we carry out i n some biological systems. We use sequences of residues/structures of proteins from biological systems (data from UNIPROT and PD B)B), and their interaction w ith ligands (small molecules and other proteins) aiming for a (molecular based) u n derstanding of the b iolog ical processes in focus, and applications aimed at the creation, improvement, repositioning, and development of drugs (sma ll m olecules and polypeptide s). In the scope of in silico and/or in vivo molecular biology, we describe in t h is thesis basic re se arch and applications developed with Candida spp in vitro ), Covid, Cancer Immunology, and Atrazine Pesticide Binding to Human Se ru m A lbumin (HSA ). They were based on the sequences of residues and struc t ures of proteins (UN IPROT and PDB), modeling of pro teins b y homology, docking in proteins (ClusPro, Frodock, and Vina), molecular dynamics in proteins and membranes (CHARMM an d GRO MA CS ), and quantum biochemistry non homogeneous dielectric function and di v ide and conquer met hodology (MFCC) of the interacti on of s mall molecules and polypeptides with the target proteins of each biological system. The activities and colaborations carri ed o ut during the development of the thesis resulted in five publications on Candida spp., si x publications on CO VID, and two p ublicat ions on the interaction of the sweetener stevia and the pesticide atrazine with HSA/BSA, which provides information on how t he se import ant molecules are carried by the blood.